Pandemia do novo coronavírus e o uso das tecnologias digitais: oportunidades e desafios para novas práticas pedagógicas na educação técnica profissionalizante de nível médio - Canado, Tania Guidotti (2022)
The year of 2020 prompted humankind to a behavioral change in multiple segments to adapt to the pandemic triggered by the new coronavirus - COVID-19, in this scenario, education suffered a major as the in-person activities were put on hold pushing the demands for the use of technological resources to ensure the continuity of the educational activities. This work proposes the investigation of the process of adapting in-person classes to remote classes model, using digital information and communication technologies (TDIC), amid the pandemic of the new Coronavirus focused on high school professional education. As a research problem, we seek answers to the following questions: how did teachers react to the urgent adaptation needs of in-person classes to a new model? what are the changes in the teachers' perception about the use of technologies in remote classes? and how do teachers assess the challenges and opportunities for digital inclusion in professional education? To support the project, we propose three objectives, as follows: (i) understand the role of digital technologies in pedagogical practice during remote classes; (ii) analyze the perception of teachers on how the use of digital resources can contribute to enhancing pedagogical practices and to build knowledge; (iii) map, from this study, the main opportunities, challenges, and experiences of the remote educational model using digital resources, during social isolation. The corpus selected for this study is the narratives of 3 (three) teachers selected to participate in the research, setting a reflection on the teaching performance in the preparation and deployment of remote classes during the pandemic, in the teaching performance of professional education. What justifies this choice, is the high increase of digital technologies used during the new Coronavirus – Covid-19 pandemic and the need to better understand the teacher and the student roles conducting activities that meet the actual society educational demands and aspirations. The theoretical framework that supports this work are studies on teacher’s education by Pimenta (2012), Tardif (2012), studies on active learning methodologies by Moran (2018), Garret (2015), study on interactive technologies by Tori (2017) and Almeida (2011) the narrative research by Clandinin and Connelly (2015), Josso (2010) and the legislation in place during the exceptional period of the pandemic. The methodology used was qualitative research applying the narrative inquiry. As a result, I present some challenges identified in pedagogical practice during remote classes, with special attention to the lack of infrastructure, lack of guidance and encouragement for new technologies adoption, lack of space sharing, and lack of teacher training in Professional Education (PE). On the other hand, it is possible to determine that this scenario contributed to highlighting some great opportunities such as the expansion of the studies about professional education, the understanding of the relevance and contributions of TDIC in Professional Education, the use of experiential knowledge in teaching practice and to emphasize the development of EP Teacher Training Programs. (AU)